The role of diabetes in metastatic melanoma patients treated with nivolumab plus relatlimab - Domenico Mallardo; Rachel Woodford; Alexander M. Menzies; Lisa Zimmer; Andrew williamson; Egle Ramelyte; Florentia Dimitriou; Alexandre Wicky; Roslyn Wallace; Mario Mallardo; Alessio Cortellini; Alfredo Budillon; et al. (Journal of Translational Medicine, 2023)
Abstract Background The combination of nivolumab + relatlimab is superior to nivolumab alone in the treatment of naive patients and has activity in PD-1 refractory melanoma. We had previously observed a reduced expression of LAG3 in melanoma tissue from patients with type 2 diabetes. Method To evaluate the impact of diabetes on oncological outcomes of patients with advanced melanoma treated with nivolumab plus the LAG3 inhibitor relatlimab we performed a retrospective multicenter study. Results Overall, 129 patients were included: 88 without diabetes before the treatment, 37 who were diagnosed with type 2 diabetes before the start of treatment, and 4 without diabetes before treatment who developed immune checkpoint inhibitor-induced diabetes (ICI-DM). PFS was 21.71 months (95% CI: 15.61–27.81) in patients without diabetes, 10.23 months (95% CI: 5.81–14.66) in patients with type 2 diabetes, and 50.85 months (95% CI: 23.04–78.65) in patients who developed ICI-DM. OS was 37.94 months (95% CI: 31.02–44.85) in patients without diabetes, 22.12 months (95% CI: 14.41–29.85) in those with type 2 diabetes and 57.64 months (95% CI: 42.29–72.99) in those who developed ICI-DM. Multivariate analysis showed that the presence of diabetes and LDH was correlated with OS and PFS. The mean OS was 64.63 months in subjects with low levels of glucose (< 137 mg/dl) and 36.27 months in those with high levels (hazard ratio 0.16, 95% CI: 0.04–0.58; p = 0.005). The patients whose glucose blood level increased after 3 months of treatment with nivolumab + relatinib compared to baseline (ratio of blood level at baseline/after 3 months > 1.5) had a worse prognosis than those whose glucose level had not increased. This result was observed also in subgroups treated either in first line or further lines. Patients who developed ICI-DM during the study period had better outcomes than the overall population and patients without diabetes. Conclusions LAG3 inhibition for treating metastatic or unresectable melanoma has a reduced efficacy in patients with type 2 diabetes, possibly due to a low expression of LAG3 in tumor tissue. Higher level evidence should be obtained.